I love baseball : players, managers, sportswriters, and fans talk about their love for the game - Stewart, Wayne, 1951- (Lyons Press, 2025)
"From zany mascots to the most beautiful ballparks ever, and from great traditions to humorous anecdotes from the game, this book explores the many reasons we love baseball. Based on assiduous research and features the author's exclusive interviews with baseball legends past and present"--